Bilgi toplumu ve bilgi işçisi bağlamında çağrı merkezleri: Emek süreci iş ve istihdam - Çetin, Işıl Başak (My University, 2005)
Bilgi ve iletişim teknolojilerindeki gelişmeler, 1980'lerde mikroelektronik alanındaki yeniliklerle birlikte hız kazanmıştır. Yeni bir toplumsal modelin, çalışma türünün ve işçi tipinin ortaya çıktığı yönündeki görüşler de, bu değişimlere eşlik etmektedir. Bu tez, bilgi toplumu varsayımlarıyla ilgili olarak ileri sürülen yeni çalıma türü ve işçi tipi tartışmalarını, Türkiye'deki özel bankaların çağrı merkezlerinde test etmeyi amaçlamaktadır. Bilgi işi ve yüksek ücretli, yüksek vasıflı bilgi işçilerinin ortaya çıktığı iddialarına karşın; elde edilen bulgular, emek süreci, iş ve istihdamın Fordist-Taylorist iş organizasyonunun temel prensiplerini içerdiğini göstermektedir. Name and Surname : Başak Işıl Çetin Field : Labor Economics and Industrial Relations Programme : Labor Economics Supervisor : Associate Professor Zeki Parlak Degree Awarded and Date : Master - July 2005 Information Society, Call Centre

CALL CENTRES IN THE CONTEXT OF INFORMATION SOCIETY and KNOWLEDGE WORKER: LABOR PROCESS WORK and EMPLOYMENT The advancements in information and communication technologies have accelerated since the 1980s along with innovations in microelectronics. An associated development was that a new model of society and a new type of work and worker were emerging. This thesis intends to test the arguments about the emergence of new type of work and workers associated with the information society thesis in the context of call centers in private banks in Turkey. It seeks to demonstrate that despite the claims about the emergence of information work and knowledge workers with high wages and skill, labor process, work and employment are designed in line with the principles of Fordist-Taylorist work organizations.
Keywords: Çağrı Merkezleri; Çalışma Ekonomisi